“I Never Thought I´d Drop out of School”. The Influence of Parents Academic History in the Development of Dual Career in the Elite Athletes - Moreno, Rubén; de Subijana, Cristina López; Chamorro, José L (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The main aim of this study is to explore the relation of the educational level of the parents in the development of the elite athletes’ dual career. For this purpose, a qualitative study was designed through personal interviews with a sample of 20 athletes (10 retired and 10 active). Subsequently, a content analysis was carried out combining deductive and inductive approaches, and different representative categories were obtained. The results show that those athletes whose parents had a higher education develop a dual career including university studies. In addition, they usually choose a university degree not linked to sports, which seems to give them a multidimensional identity that facilitates the withdrawal of their sporting career. On the other hand, athletes whose parents did not have higher education, when they opt for a dual career, they do so by studying university degrees linked to sports, officially and non officially sanctioned-non regulated by law nor approved by the Education Ministry. This favors a one-dimensional identity exclusively focused on sports, hampering the transition to the athletic retirement.